(untitled) (Research, Society and Development, 2023)
National Curricular Guidelines (NCGs) for the Medical Course highlighted the profile that the physician upon graduation must present, and should exercise his profession as a generalist, humanize the relationships with the people to whom he offers care, being able to reflect, criticize about their practices, in an ethical way. Objective: To reflect, through student practice, whether the teaching of the medical course is being able to train professionals with the profile of the general practitioner present in the DCNs for the medical course. Method: This study is an experience report of the third-period students of the IESC 3 Discipline of the Medical Course of UNIGRANRIO-AFYA. Results: The realization of the PTS, a valuable tool of the interdisciplinary team in primary health care, involves them together with the team in care, designating functions and objectives, seeking attention to integral and resolutive care, to involve the appropriate actors for better adherence and quality of life to users. Conclusion: The practices conducted in IESC 3 having as allies the practices of HAM 3 and the lectures that take place in both axes are contributing to the continuation of the development of skills to act in Primary Care in a critical and reflective way.